Controller Tuning for an Object with Astatism of 2nd Order for Learning Purposes; Technology Enhanced Learning in Higher Education (TELE2023) - Lyapunov D. Yu. Danil Yurievich; Lyapushkin S. V. Sergey Viktorovich; Shilin A. A. Aleksandr Anatoljevich; Domaratskaya M. P. Margarita Pavlovna; Yudintsev A. G. Anton Gennadjevich (2022, 2022)
Title screen